Development of multi-channel video & sound integration system for measurement of ability of badminton players to predict shuttlecock hit - Lee, S.-Ch.; Goo, H.-M. (International Journal of Applied Sports Sciences, 2007)
Many different types of measurement devices are used to study the motions of athletes. Among them, those that use recorded videos are widely used because they are relatively convenient to use and can store a large volume of information. However, it often happens that general video equipment such as video camera cannot be used depending on the subject of study, the development of devices with features appropriate for the purpose of study is frequently needed. Accordingly, this study investigated the development of the multi-channel video & sound integration system as part of a research on development of specialized devices. The system developed from this study has the feature to receive images simultaneously from four cameras and display them on one screen and record them, and the feature to accurately capture the hitting moment of the badminton shuttlecock and display it as an integrated image. To minimize the time and cost for manufacturing it, the COTS (Commercial Off The Shelf) technique, which is widely used in the system development field, was used. The manufactured system was used in an experiment to study the strategies to improve the ability of single badminton players to predict the shuttlecock hit by the opponent, and the video data for about 35 players were created and used as the basic data of the study.